Prevalence of epilepsy in Hawler city; a household survey - Khidr, Azad Hasan; Sheikh-Bzeni, Aso Sabir (Zanco Journal of Medical Sciences (ZJMS), 2011)
Background and objectives: Epilepsy is a common neurological disorder and in spite of that, its prevalence was not studied in Hawler city before. The objective of this study is to know the prevalence of epilepsy in Hawler city. Methods: A house hold survey was carried out in Hawler city, Iraq 4623 persons selected as clustered random sample of the city population during period of April 2007 to June 2008. Results: Out of the 4623 persons studied, only 45 patients (23 female and 22 male) were found to be epileptic, with a life time prevalence of 9.7/1000 population. The commonest age group affected was childhood age (1st and 2nd decade). This study showed that partial epilepsy was more common than generalized epilepsy. There is no marked difference between genders in the disease pattern (51.1% were females, 48.9% were males). Conclusion: Epilepsy is a common disorder in Hawler city. There was no significant difference between genders in the disease pattern. In our locality children were more affected with epilepsy than other age groups.